The Effect of Rice Washing Water and Lactobacilus Bacteria on the Growth and Production of Mustard PlantsEffect of Leri Water and Lactobacilus Bacteria on Growth and Mustard Crop Production - M Abror (Nabatia, 2018)
Rice water is very high in carbohydrates and protein. But much of it is thrown away and not used. This is an alternative material for making liquid organic fertilizer. To be able to take advantage of the water, you need lactobacillus bacteria to break it down. Cow's milk contains lactobacillus bacteria which function as decomposers. With a combination of lactobacillus bacteria with rice water, it will be a good organic fertilizer.The purpose of this research was to determine whether leri water and lactobacillus bacteria could be used as liquid organic fertilizers, to determine whether leri water and lactobacillus bacteria had an effect on the growth and production of mustard plants, to determine the nutritional content of mustard plants which were given liquid organic fertilizer with inorganic. The study was conducted in February 2017 - May 2017 with a randomized block design (RBD) with 6 levels and repeated 5 times. The parameters observed were the number of leaves, weevil diameter, plant length, total wet rice, accumulative selling weight and nutritional content of mustard greens. The analysis used was analysis of variance and continued with the 5% BNJ test. Based on the results of data analysis and conclusions, it can be concluded that leri water and lactobacillus bacteria have an effect on the growth and production of mustard greens. In the K5 treatment (5 cc / liter) has a significant effect on all observations. K6 (inorganic fertilizer) gets the highest value because it is a comparison for liquid organic fertilizers